Pengaruh Pemberian Booklet Kepada Caregiver Terhadap Perubahan Persepsi Beban Pengasuhan Pada Orang Dengan Gangguan Jiwa Di RS Jiwa Naimata Kota Kupang - Maria Fatima Saga Wea; Fitri Handayani; Johana Art Cindy Peny (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
Family is the closest person to the patient who has an important role in the patient's recovery. Families are needed to treat people with mental disorders with a positive attitude, can provide support for the growth of hope and optimism. The role of the family in trying to prevent recurrence can be done by providing motivation, being a good listener, providing recreation, and being responsible for treatment and care. This type of research is quasi-experimental with one group pretest design. The sampling method in this study is purposive sampling. Respondents in this study were family members who became caregivers for people with mental disorders at Naimata Hospital with a total of 52 respondents. Data analysis in this study used the T-Test. The research was conducted at Naimata Mental Hospital Kupang City. Data collection will be carried out in August - October 2023. The results showed no relationship between knowledge and attitudes with TB prevention behavior with a p value of > 0.05. Conclusion: there is an effect of Booklet giving to Caregivers on changes in the perception of Caregiver Burden on ODGJ RS Jiwa Naimata Kota Kupang.